2012
DOI: 10.3174/ajnr.a3329
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acute Vertebrobasilar Occlusion Using Thrombectomy with Stent Retrievers: Initial Experience with 18 Patients

Abstract: BACKGROUND AND PURPOSE:Acute vertebrobasilar occlusion is an ominous disease with few proved effective treatments. Experience with stent retrievers is scarce and limited to combined therapies (stent retrievers associated with previous intravenous fibrinolysis, intra-arterial thrombolysis, or other mechanical devices). We present our experience with 18 patients treated with direct thrombectomy by using stent retrievers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
42
3
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 23 publications
6
42
3
1
Order By: Relevance
“…Recent studies with the use of mechanical thrombectomy with stent retrievers reported significantly increased recanalization rates ranging from 74 -100% in patients with acute BAO. [12][13][14] In our study, we achieved successful recanalization (TICI grades 2b to 3) in 96% (24/25) of patients, which is in line with previous reports. Successful recanalization with only the Solitaire stent occurred in 84% (21/25) of patients.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Recent studies with the use of mechanical thrombectomy with stent retrievers reported significantly increased recanalization rates ranging from 74 -100% in patients with acute BAO. [12][13][14] In our study, we achieved successful recanalization (TICI grades 2b to 3) in 96% (24/25) of patients, which is in line with previous reports. Successful recanalization with only the Solitaire stent occurred in 84% (21/25) of patients.…”
Section: Discussionsupporting
confidence: 80%
“…[12][13][14] In contrast to our study, these previous studies included patients treated within 24 hours of stroke symptom onset. In a series of 14 patients treated with a Solitaire thrombectomy, Mordasini et al 12 reported that 28.6% (4/14) had a good outcome (mRS 0 -2), and the mortality rate was 35.7% (5/14).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…3 Early recanalization remains the main important factor that can improve outcome. [4][5][6] However, even though the best recanalization rate is achieved by using a newer stent retriever, such as a Solitaire FR Device (Covidien, Irvine, California) (up to 100%), [7][8][9][10] stent retriever impact on functional outcome is not as clear-cut as expected and has not been documented in a randomized trial. The extent of baseline brain stem ischemic damage can also influence outcome.…”
mentioning
confidence: 99%